A guide to sports and injury management - Bundy, Mike.; Leaver, Andy. (Edinburgh : Churchill Livingstone Elsevier, 2010)
The DVD features a unique interactive diagnostic aid for common injuries, 60 narrated videoclips of examinations and exercise demonstrations, and multiple-choice questions for self-testing. --Book Jacket.
Training and conditioning -- Injury prevention -- Nutrition -- Drugs and sport -- Musculoskeletal injury -- Return to sport -- Exercise and illness.
Book is acconpaied by one DVD ROM'A Guide to sport and injuries management' bearing the same call number and available at Makmal Digital, Perpustakaan dr. Abdul Latiff, KKL.
Book is accompanied by one DVD-ROM'A guide to sports and injury management' bearing the same call number and available at Koleksi Media, Perpustakaan PPUKM.
Keywords: Athletic Injuries -- prevention & control; Physical Therapy Modalities; Sports medicine